KORELASI PRODUKTIVITAS PETANI KELAPA DENGAN KESEJAHTERAAN KELUARGA DI KELURAHAN SUNGAI PERAK KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - ", Nurhakiki; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to determine the Correlation of Productivity of Coconut Farmers with Family Welfare in Sungai Perak Village, Tembilahan District, Indragiri Hilir Regency. The sampling technique in this study was stratified random sampling. To be more representative of the researchers taking a sample of 65 respondents with a calculation of 10 percent of the total population in each number of coconut farmers based on the number of coconut trees owned. Data collection techniques used were questionnaire sheets and direct observation. This study uses quantitative methods, presented in table form and then given an explanation. The statistical test used is the Pearson product moment correlation test, and the data obtained is processed using SPSS 23.0 for Windows. Based on the results of the research conducted, it was concluded that the productivity and welfare of the families of the coconut farmers were categorized as being moderate. This is proven by calculating an interval value that is at a moderate interval (2,384-3,337). The proposed hypothesis produces a correlation of productivity of coconut farmers with family welfare in Sugai Perak Village, Tembilahan District, Indragiri Hilir Regency. Keywords: Productivity, Family Welfare, Correlation, Coconut Farmers